Resolutions of the Chambers of the Polish Parliament (Sejm and Senate) on Recognition of Russia as a Terrorist State in Light of the Practice of Parliamentary Assembly of the Council of Europe and European Parliament (Polish Yearbook of International Law, 2023)
The Parliament of the Republic of Poland was one of five European parliaments which – in view of the full-scale aggression by Russia against Ukraine which commenced on 24 February 2022 – adopted resolutions declaring the Russian Federation as a state associated with terrorism. The Polish acts are consistent with resolutions adopted on the same subject by the Parliamentary Assembly of the Council of Europe (PACE) and the European Parliament of the European Union (EP).Although not legally binding, the adoption of these resolutions have a large symbolic dimension and may have a negative impact on the perception of and possibilities of Russian participation in the international arena. From the Polish perspective, the national decisions linking Russia with terrorist activities will influence decisions taken within the sanctions regime, as well as with regard to the legal qualification of certain acts under Polish criminal law in the course of proceedings conducted by Polish prosecution authorities in relation to the war. Finally, as long as the war continues and the assessment of Russia as a terrorist state remains in place, it will not be possible to restore and maintain ordinary diplomatic, economic and other relations with that state.